Investigation on Influential Social and Economic Factors on Citizen's Participation in Urban Affairs Related to Municipality - yousef amini; mohammad amini (توسعه اجتماعی, 2017)
The research aims to study about influential social and economic factors on citizens participation in urban affairs related to municipality among citizens who are older than 18 years and are resident in Shoushtar. It is about citizen's participation dimensions and its factors. Its theoretical literature is based on psychological and sociological perspectives. Research method is survey. Also documents and library sources and structured questionnaire as information gathering instrument have been used. Cluster sampling method has been used and 373 have been determined as population sample by using Cochran formula. Findings show that there are positive, direct and significant relationship between citizen's satisfaction, social trust, feeling of social belonging, and citizen's awareness and income as independent variables and dependent one. On the other hand, the more satisfaction, trust, awareness, feeling of belonging and citizens income, the more citizens participation. The findings approve the different participation between employed and unemployed. Also, the average score of social participation among different classes statistically and based on F test is significant. That is, rate of participation in middle and upper classes are more, meanwhile, the period of residency in city is so important variable so that the more period of residency in city, the more citizens social participation.